Wet Chemical Synthesis of Non-solvated Rod-Like α'-AlH3 as a Hydrogen Storage Material - Liu, Haizhen; Ma, Hongyu; Zhang, Longfei; Gao, Shichao; Wang, Xinhua; Xu, Li; Liu, Shuangyu; Huang, Xiantun; Lu, Chenglin; Luo, Hui; Ning, Hua; Lan, Zhiqiang; et al. (Frontiers in Chemistry, 2020)
Aluminum hydride (AlH3) is a promising candidate for hydrogen storage due to its high hydrogen density of 10 wt%. Several polymorphs of AlH3 (e.g., α, β, and γ) have been successfully synthesized by wet chemical reaction of LiAlH4 and AlCl3 in ether solution followed by desolvation. However, the synthesis process of α'-AlH3 from wet chemicals still remains unclear. In the present work, α'-AlH3 was synthesized first by the formation of the etherate AlH3 through a reaction of LiAlH4 and AlCl3 in ether solution. Then, the etherate AlH3 was heated at 60°C under an ether gas atmosphere and in the presence of excess LiAlH4 to remove the ether ligand. Finally, α'-AlH3 was obtained by ether washing to remove the excess LiAlH4. It is suggested that the desolvation of the etherate AlH3 under an ether gas atmosphere is essential for the formation of α'-AlH3 from the etherate AlH3. The as-synthesized α'-AlH3 takes the form of rod-like particles and can release 7.7 wt% hydrogen in the temperature range 120–200°C.